Can finger-prick sampling replace venous sampling to determine the pharmacokinetic profile of oral paracetamol? - Mohammed, Baba S (Blackwell Science Inc, 2010)
The drive to increase the availability of paediatric pharmacokinetic data with minimum blood loss has led to the development of micro-sampling techniques. However studies have suggested that pharmacokinetic data from venous or capillary blood samples may not be directly comparable. AIM: The aim of this study was to determine whether paracetamol demonstrates concentration differences between finger-prick and venous blood samples. METHODS: Paired finger-prick and venous blood samples were taken at 0, 15, 30 and 60 min following 1 g oral paracetamol, from 12 male adult subjects. Paracetamol concentration was determined using HPLC and UV detection with a LLOQ of 2200 pg on column. Intra-assay coefficient of variation for paracetamol at the LLOQ was 3%. RESULTS: At 15, 30, and 60 min post dose the median finger-prick paracetamol concentration was 349%, 72%, and 9.3% greater than the equivalent venous concentrations, respectively. Regression analysis confirmed a significant relationship between finger-prick and venous paracetamol concentrations at 15 min (r(2) = 0.81, P = 0.006), at 30 min (r(2) = 0.82, P < 0.0001) and at 60 min (r(2) = 0.87, P < 0.0001) post dose. The regression equation for venous and finger-prick blood concentrations at 15, 30 and 60 min post dose were Venous(15) = Finger(15) − 3.4, Venous(30) = Finger(30) − 3.4 and Venous(60) = 0.68Finger(60) + 3.06, respectively. CONCLUSIONS: Paracetamol demonstrates an arteriovenous difference in concentration, and the use of finger-prick samples may give rise to results which differ from those obtained with traditional venous sampling especially during the first 1 h following drug ingestion.